ANALISIS KEMAMPUAN LITERASI MATEMATIS DALAM MENYELESAIKAN SOAL CERITA OPERASI HITUNG PECAHAN DITINJAU BERDASARKAN GAYA BELAJAR HONEY-MUMFORD - Manapa, Imanuel Yosafat Hadi; Waang, Serlina Magdalena (Jurusan Pendidikan MIPA FKIP Universitas Pattimura, 2025)
This study aims to describe the mathematical literacy ability of students in solving fractional counting operation story problems based on the Honey-Mumford learning method. The subjects of this study are students of class V of SD GMIT Pulelang. The instruments used in data collection were the mathematical literacy test instrument and the Learning Style Questionnaire (LSQ). The results of the study show that there are differences in students' abilities in several aspects based on indicators in mathematical literacy. Students with an activist learning style tend to be more detailed in terms of formulating problems in detail using correct mathematical sentences, using the right procedures but not to the stage of simplification and the conclusions given are not precise. Students with a reflective learning style tend to be meticulous in using proper calculation operating procedures and deduce the final result correctly and to formulate problems tend to use practical mathematical sentences. Students with a theoretical learning style tend to solve problems carefully using the right procedures and reinterpret the meaning of the question but it is not incomplete. Furthermore, students with a pragmatic learning style tend to use simple and practical reasoning with the use of minimal mathematical formulas so that the final results obtained are more predominantly wrong